Management and information technology after digital transformation - Dahlin, Peter; Keller, Christina 1961-; Ekman, Peter 1969- (Routledge studies in innovation, organizations and technology, 2022)
"With the widespread transformation of information into digital form throughout society - firms and organizations are embracing this development to adopt multiple types of IT to increase internal efficiency and to achieve external visibility and effectiveness - we have now reached a position where there is data in abundance and the challenge is to manage and make use of it fully. This book addresses this new managerial situation, the post-digitalization era, and offers novel perspectives on managing the digital landscape. The topics span how the post-digitalization era has the potential to renew organizations, markets, and society. The chapters of the book are structured in three topical sections but can also be read individually. The chapters are structured to offer insights into the developments that take place at the intersection of the management, information systems and computer science disciplines. It features more than 70 researchers and managers as collaborating authors in 23 thought-provoking chapters. Written for scholars, researchers, students and managers from the management, information systems and computer science disciplines, the book presents a comprehensive and thought-provoking contribution on the challenges of managing organizations and engaging in global markets when tools, systems and data are abundant"--